Cytotoxicity of Kelakai (Stenochlaena palustris) Extract to MCF-7 Breast Cancer Cell - Harlyanti Muthma'innah Mashar; Itma Annah (Jurnal Fitofarmaka Indonesia, 2020)
Breast cancer is reported to rank fifth among all types of cancer with a case of death of 6.6%. In the Central Kalimantan region, early examinations of cancers including breast cancer were carried out and 247 tumors in the breast were identified (1.76%). Kelakai (Stenochlaena palustris) as one of the typical plants of Kalimantan which contain natural chemical constituents has been reported to be effective as an anti-inflammatory and antioxidant, so that with this potential can be developed to overcome diseases associated with it, one of them is breast cancer. This study aimed to examine the cytotoxicity of MCF-7 breast cancer cells using ethanol extract. The cytotoxicity assay of kelakai extract against MCF-7 cells conducted in vitro by the MTT reduction method. The variation of concentration used is 1000; 500; 250; 125; 62.5; 31.5; and 15.625 µg/ml, doxorubicin as a positive control was performed in a concentration of 1 μg / ml. The results of the cytotoxicity assay showed that the kelakai extract had a toxic effect on MCF-7 cells with an IC50 value of 493.57 µg / ml.